O ESPAÇO GEOGRÁFICO: UM ESFORÇO DE DEFINIÇÃO - Braga, Rhalf Magalhães (Programa de Pós-Graduação de Geografia Humana e Programa de Pós-Graduação de Geografia Física, 2007)
Since the beginning as a modern science, Geography faces epistemological and conceptual problems. It´s the case of the definition of its study object: the geographical space. Unlike the recent theory advances, still exists doubts about it. So, the purpose of this text is to comment some tries to define geographical space and, in the end, propose our own concept. We understand that geographical space is the continuous result of social-spatial relations and these relations are economical (society-space relation through work), political (society-State relation or relations between National States) and cultural/symbolic (society-space relation through language and imaginary).